Primary Congenital Glaucoma: A Novel Single-Nucleotide Deletion and Varying Phenotypic Expression for the 1546-1555dup Mutation in the GLC3A (CYP1B1) Gene in 2 Families of Different Ethnic Origin - Chavarría Soley, Gabriela (2003)
Artículo científico -- Universidad de Costa Rica, Instituto de Investigaciones en Salud. 2003. Este documento es privado debido a limitaciones de derechos de autor.